SUPERVISI DALAM AL-QUR’AN: STUDI TERHADAP PRINSIP-PRINSIP DAN SASARAN PENGAWASAN DALAM KONTEKS PENDIDIKAN ISLAM - Sesi Meriana; Anik Faseha; Khairul Azan (STAIN Bengkalis, 2024)
Supervision is one of the important things that must be done in education. The important role of supervision that focuses on the principles and objectives in Islamic education is increasingly significant in the face of dynamic changes in the world of education that continues to grow. This study aims to examine what is meant by supervision and supervision and its principles in the context of Islamic education to the objectives of educational supervision. The method used in this research is using Literature Review study or literature review by using data collection techniques in the form of quotations from various sources, such as books, scientific journal articles. Meanwhile, the data analysis technique used is descriptive analysis to detail and describe the relevant findings from the literature reviewed. The results show that the study of the principles of supervision in the context of education is as follows: (1) Scientific Principles, (2) Deliberative Principles, (3) Cooperative Principles, (4) Constructive Principles, (5) Principles of Responsibility, (6) Principles of Prudence in Decision Making. The targets of supervision and supervision in education are carried out in order to improve the quality of the learning process which includes: (1) Curriculum Development and Guidance, (2) Learning Improvement and Refinement, and, (3) Teacher and School Staff Resource Development.